Implementation of Restorative Justice in the Police in Realizing a Just Legal State - Fiesta Aulia Rizka (Law Research Review Quarterly, 2024)
The upholding of justice, as well as  usefulness and  certainty of  the law are the fundamental goals of  the law that was created. However, in thiscase  it also turns out that in reality it is difficult to realize it together. The police have an active role and participate in enforcing the law in Indonesia, especially regarding matters the might damage Indonesian  public order. Restorative  justice ha the main aim of seeking justice in it, namely by focusing on peace efforts by prioritizing return or restoration to the initial overall state. Restorative justice this is to restore a situation  to b e better   in people's lives, not to take revenge  for a crime or crime committed. With the existence of restortive justice, it is hoped that it wil be  able to create a just legal state as mandated by the Indonesian Constitution.